Surface protection of fluoroindate glasses by sol-gel dip-coated SnO2 thin layers - Rizzato, A. P.; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Messaddeq, Younes [UNESP] (Elsevier B.V., 1999)
SnO2 coatings were deposited by a sol-gel dip-coating process to shield fluoroindate glasses (40In-F-3:16BaF(2):20SrF(2):20ZnF(2):2NaF:2GaF(3)) against corrosion in aqueous environments. The effect of the number of coating applications and of the withdrawal speed on the thickness, density and roughness of tin oxide films was investigated by X-ray reflectivity. Film thickness increases both with the number of coating applications and the withdrawal speed. The aqueous leaching of uncoated and SnO2-coated fluoroindate glasses was studied by scanning electron microscopy (SEM) and infrared spectroscopy (FTIR), showing that the glass surface was protected against hydrolytic attack. (C) 1999 Elsevier B.V. B.V. All rights reserved.